Tracking niche variation over millennial timescales in sympatric killer whale lineages - Foote, A.; Newton, J.; Avila-Arcos, M.; Kampmann, M.; Samaniego, J.; Post, K.; Rosing-Asvid, A.; Sinding, M.; Gilbert, Thomas (Royal Society, 2013)
Niche variation owing to individual differences in ecology has been hypothesized to be an early stage of sympatric speciation. Yet to date, no study has tracked niche width over more than a few generations. In this study, we show the presence of isotopic niche variation over millennial timescales and investigate the evolutionary outcomes. Isotopic ratios were measured from tissue samples of sympatric killer whale Orcinus orca lineages from the North Sea, spanning over 10 000 years. Isotopic ratios spanned a range similar to the difference in isotopic values of two known prey items, herring Clupea harengus and harbour seal Phoca vitulina. Two proxies of the stage of speciation, lineage sorting of mitogenomes and genotypic clustering, were both weak to intermediate indicating that speciation has made little progress. Thus, our study confirms that even with the necessary ecological conditions, i.e. among-individual variation in ecology, it is difficult for sympatric speciation to progress in the face of gene flow. In contrast to some theoretical models, our empirical results suggest that sympatric speciation driven by among-individual differences in ecological niche is a slow process and may not reach completion. We argue that sympatric speciation is constrained in this system owing to the plastic nature of the behavioural traits under selection when hunting either mammals or fish.